SOCIAL VALUES REFLECTED FROM TOKYO REVENGERS LIVE-ACTION MOVIE - Anggun Purnomo Arbi (Yayasan Hurriah, Banda Aceh, 2022)
A good movie is one that is able to convey useful messages in social life. The researcher assumes that Tokyo Revengers Live-Action is a movie that presents social values. In other words, this research has the objective of analyzing and describing the types of social values contained in this movie. In conducting this research, the researcher applied a qualitative descriptive research method. The research instrument is divided into two parts: researchers and documentation. The film scene and scripts from Tokyo Revengers are the object of this research. In the data collection process, the researcher implemented the documentary method. Meanwhile, in the process of data analysis, researchers used content analysis methods. The researcher found that, in the Tokyo Revengers live-action movie, there are three types of social values, including affection, responsibility, and life harmony.